Analisis Penggunaan WhatsApp Sebagai Media Pembelajaran Bahasa Arab di Era Industri 4.0 - Mustofa, Muhammad Arif (Arabiyatuna: Jurnal Bahasa Arab, 2020)
The purpose of this study is to describe the use of Whatsapp in learning Arabic and the principles of media selection in the era 4.0. The digital era or commonly known as the industrial era 4.0, learning that runs must use technology that makes it easier for teachers and students to carry out the teaching and learning process, as well as learning Arabic. Whatsapp as a medium that is widely used today can be used for learning Arabic. This research is library-based, so that the data obtained through deepening the text of books or articles is in accordance with the required data. Then the data were analyzed and described. This article provides an answer by explaining that the principles of media selection in the 4.0 era are clarity of media intentions, familiarity, and clear guidelines for their use. The use of Whatsapp for learning Arabic using the Whatsapp group and unbeatable text, voice, video and file messaging services with language skills that will teach.